2020
DOI: 10.15560/16.2.451
|View full text |Cite
|
Sign up to set email alerts
|

First record of the Lesser Long-nosed Bat, Leptonycteris yerbabuenae Martinez & Villa-R., 1940 (Chiroptera, Phyllostomidae), in Nicaragua

Abstract: We report the first record of the Lesser long-nosed Bat, Leptonycteris yerbabuenae Martinez & Villa-R., 1940 in Nicaragua based on a specimen from San Nicolas, Estelí Department, north-central Nicaragua. The new record extends the known range of this large, migratory, nectar-feeding species 100 km southeast from the closest previous record in western Honduras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…First, there have been very few records of this species in Honduras and Central America in general; in addition, there have been no recent records for this species in Honduras at all. Second, this species was previously only known to occur at low elevations in Honduras (although up to 1291 m in Nicaragua; Saldaña Tapia et al 2020). Now, we know that the long-nosed bat inhabits highlands in Honduras (up to 1710 m at Cerro de Hula, Table 1).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…First, there have been very few records of this species in Honduras and Central America in general; in addition, there have been no recent records for this species in Honduras at all. Second, this species was previously only known to occur at low elevations in Honduras (although up to 1291 m in Nicaragua; Saldaña Tapia et al 2020). Now, we know that the long-nosed bat inhabits highlands in Honduras (up to 1710 m at Cerro de Hula, Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…A third record for the lesser long-nosed bat in Honduras from Francisco Morazán was included in fig. 2 by Saldaña-Tapia et al (2020), referring to an additional iNaturalist record https://www.inaturalist.org/observations/20857871 (O. Saldaña-Tapia, pers. comm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent efforts to study bats in the Mesoamerican region have increased the number of bat species known. For example, Kraker-Castañeda et al (2016) listed 100 species for Guatemala, Mora et al (2018) and Turcios-Casco et al (2020a) increased the list for Honduras to 111 plus four expected species and recently, Medina-Fitoria and Martínez-Fonseca (2019) and Saldaña Tapia et al (2020) increased the list for Nicaragua to 111 species. In addition, York et al (2019) reported 120 for Costa Rica.…”
Section: Introductionmentioning
confidence: 99%